Sharing cities. Activating the urban commons. - (:unkn) unknown (Shareable, 2018)
Cities are a key driver of the most urgent challenges societies face today including inequality, racism, social isolation, and climate change. Not to mention that billions of city dwellers are often unable to meet their basic needs for food, water, and housing. Amidst this crisis lies tremendous opportunity for people to address these challenges together. Communities, organizations, and local governments are increasingly responding to challenges by reviving a basic human practice: sharing. By sharing their labor, space, goods, and more, people are overcoming scarcity by building and maintaining vital common resources. They show that sharing can lead everyone to have more, together."Sharing Cities" showcases over a hundred sharing-related case studies and model policies from more than 80 cities in 35 countries. It witnesses a growing global movement and serves as a practical reference guide for community-based solutions to urgent challenges faced by cities everywhere. This book is a call to action meant to inspire readers, raise awareness, and strengthen the sharing movement worldwide. The book shows that not only is another world possible but that much of it is already here.
Keywords: Stadtentwicklung; Stadtgesellschaft; Gemeinschaftsnutzung; Öffentliches Gut; Sharing Economy